Sustentabilidade no beneficiamento têxtil: produção de tingimentos com reuso de efluente tratado por fotocatálise via UV/H2O2 - Rosa, Jorge Marcos (2010)
The aim of this work was to verify the reuse possibility of treated textile wastewater by homogeneous photocatalysis via UV/H2O2. The photocatalytic process was performed in a kind of boatload reactor containing two UV-C lamps, 237nm, 6W each, at 296K under magnetic stirring. Initially were tested three types of dyes present in synthetic wastewater. All dyeing were done at "Francisco Matarazzo SENAI School Laboratory and all wastewater photochemical decomposition test had efficiency above 90%. After those tests with synthetic wastewater, were collected two real wastewater samples from a dyeing room, in which were done nine decomposition process with aid of a factorial planning 23. After the analysis of the results, the best process was selected to be applied in order to realize five consecutive dyeing, all of them with photochemical decomposition treatments results above 85%. The dyeing made with wastewater were tested against dyeing made with water, with satisfactory results, all with total deviations below DE = 1.10, showing that the process can be applied in order to reuse the treated wastewater it in new dyeing processes.